THE SEVERE COURSE OF DRUG THERAPY-RESISTANT ANKYLOSING SPONDYLITIS - D. G. Rumyantseva; M. V. Podryadnova; O. A. Rumyantseva; M. M. Urumova; Sh. Erdes (Научно-практическая ревматология, 2020)
At present, there is more and more evidence in rheumatology on the factors influencing the efficacy of biological agents (BAs), and there is no generally accepted algorithm for managing patients resistant to standard therapy. The paper describes three patients with ankylosing spondylitis (AS) who were followed up at the V.A. Nasonova Research Institute of Rheumatology in 2011–2019. All the patients showed a severe course of AS of high clinical and laboratory activities, extra-articular manifestations, and inefficacy of three or more BAs. All the patients share the following symptoms: male gender, early onset of disease, high clinical and laboratory activities, and extra-articular manifestations, such as uveitis and psoriasis.